C is for cowboy : a Wyoming alphabet - Gagliano, Eugene M.; Guy, Susan, 1948- (Chelsea, MI : Sleeping Bear Press : Thomson/Gale, 2005)
A rhyming alphabet that names people, places, and things from Wyoming's history, culture, and natural world and provides background information on each one.
4.4
K-3
Keywords: Wyoming -- Juvenile literature; English language -- Alphabet -- Juvenile literature; Wyoming; Alphabet; Wyoming; Alphabet